2019
DOI: 10.1007/s00429-019-01859-z
|View full text |Cite
|
Sign up to set email alerts
|

Variability and directionality of inferior olive neuron dendrites revealed by detailed 3D characterization of an extensive morphological library

Abstract: The inferior olive (IO) is an evolutionarily conserved brain stem structure and its output activity plays a major role in the cerebellar computation necessary for controlling the temporal accuracy of motor behavior. The precise timing and synchronization of IO network activity has been attributed to the dendro-dendritic gap junctions mediating electrical coupling within the IO nucleus. Thus, the dendritic morphology and spatial arrangement of IO neurons governs how synchronized activity emerges in this nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…Cluster sizes were similar between D0 and D7 samples (8.3 ± 0.4 and 8 ± 0.5 pixels, corresponding to 20507 square µm and 21868 square µm areas for D0 and D7, respectively; t = 0.43, p = 0.66). These characteristics are in line with previously-reported reconstructions of IO cells (Rekling et al, 2012;Kølvraa et al, 2014;Vrieler et al, 2019).…”
Section: Longer Labeling Period Enhances Signal-to-noise Ratio Of Flusupporting
confidence: 92%
“…Cluster sizes were similar between D0 and D7 samples (8.3 ± 0.4 and 8 ± 0.5 pixels, corresponding to 20507 square µm and 21868 square µm areas for D0 and D7, respectively; t = 0.43, p = 0.66). These characteristics are in line with previously-reported reconstructions of IO cells (Rekling et al, 2012;Kølvraa et al, 2014;Vrieler et al, 2019).…”
Section: Longer Labeling Period Enhances Signal-to-noise Ratio Of Flusupporting
confidence: 92%
“…However, the interaction between ION and NO neurons involves additional connections, such as the projections from climbing fibers to NO neurons (73), which are currently neglected in our model and may contribute a negative feedback to the ION neurons. In addition, the specific localization of the NO synapses on the ION neurons and the morphology of the dendrites of ION neurons may significantly steer the synchronization within the inferior olivary nucleus (72,(74)(75)(76). Accordingly, it is plausible that the NO-ION connectivity may affect the network oscillations.…”
Section: Slow-decaying Gabaergic Currents In the Dentate Nucleus Contmentioning
confidence: 99%
“…It has been shown that in the anesthetized state both the amplitude and phase of the STOs can be altered by synaptic inputs [10]. Inhibitory inputs to the inferior olive originate in the cerebellar nuclei and have broadly distributed terminals onto compact sets of olivary cells [5153]. Excitatory terminals predominantly originate in the spinal cord and lower brainstem, mainly carrying sensory information, and in the nuclei of the meso-diencephalic junction in the higher brainstem, carrying higher-order input from the cerebral cortex (Fig 1A) [15, 54, 55].…”
Section: Introductionmentioning
confidence: 99%